Supply chain analysis Maratex Manufacturing Corp. - Barro, Jesselyn; Bularan, Melanie; Chu, Ma. Rosario; Tiu, Venice (College of Engineering, 2001)
The study taxes us to the supply chain management aspect of the company, which spans through purchasing, inventory management, manufacturing, warehousing, delivery and customer service. The whole supply chain study contends with the inbound and outbound of the supplies within the company. The study started with documenting the different processes in the different element of the supply chain. The elements were classified into (1) Purchasing, (2) Warehousing/Inventory Management, (3) Manufacturing, (4) Finished Goods/Transport Operations and (5) Customer Service. In identifying the problems experienced by the company the study narrowed down these to (1) Lack of forecasting techniques, (2) Inefficient supplier selection process and (3) Lack of an information system. The study recommends that the company should utilize seasonal index as a forecasting tool because the company experiences seasonal trends in their demand. The supplier selection process recommendation explains that the company needs to adopt a new supplier selection process such as promoting supplier relationship into partnership that will lead to higher level of incoming quality, reduced lead time, higher delivery reliability, quality assurance and increase efficiency. The supplier evaluation uses criteria such as quality, cost, capacity, and delivery time/readability and management capability. The last recommendation which is to have an integrated information system that will address the record keeping and report generation in the company. The information system will include a procurement module, customer service module and an inventory management module. Each module can be a stand-alone but there are integrated to have accurate updates. Also the development of an E-Commerce system would be beneficial to the company as it tries to gear up for the 21st century in doing business. E-Commerce could lead to improvements in Marketing and Sales, Customer Service, Procurement/Transportation/Logistics and Replenishment and Inventory Management. The entire recommendation is planned to be implement within a span of two months. Some recommendations shall be maintain to keep records, update the company in current trends and production planning with the help of forecasting. After implementation, the researchers shall again study the company for any improvement brought about by the recommendation.